Correction: Evidence-based scientific exercise guidelines for adults with spinal cord injury: an update and a new guideline. Issue 11 (November 2018) - Ginis, Kathleen; Scheer, Jan; Latimer-Cheung, Amy; Barrow, Andy; Bourne, Chris; Carruthers, Peter; Bernardi, Marco; Ditor, David; Gaudet, Sonja; Groot, Sonja; Hayes, Keith; Hicks, Audrey; et al.
Authors Victoria L. Goosey-Tolfrey and Karen M. Smith were listed under the incorrect affiliations at the time of publication.